CONCEPT OF SEMANTIC FIELD AND THEORETICAL APPROACHES OF LINGUISTS - Khudaybergenova Gulbakhor Shukhrat kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Analysis of the definitions of the semantic field shows that the criterion for the interconnection of lexical units and their inclusion in one or another group is “lexical meanings as a whole”, “semantic feature”, “family antique sign”, different meanings of a word or variants of its meaning, components of meaning, etc. Such a general element can also be a concept, a theme, or a certain situation. This article examines theoretical concepts and methodological approaches in the study of the semantic field, which by its name covers very heterogeneous phenomena.